Bacterial Crown Gall of Roses Caused by Agrobacterium tumefaciens - Kamil Duman; Susannah da Silva; Fanny Iriarte; Barron Riddle; Gary Knox; Matthew Orwat; Shawn Steed; E. Vanessa Compoverde; Jeffrey Jones; Mathews Paret (EDIS, 2018)
Rhizobium radiobacter (also known as Agrobacterium tumefaciens), has been reported to be found on more than 600 different plant species worldwide including many common vegetables, weeds, deciduous and evergreen trees and shrubs. This document discusses the biology, symptom expression, and management of this bacterium.